Central mechanisms of auditory perception: neuroanatomical bases and clinical manifestations in dementia - VOLYNETS, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Hearing is one of the key sensory systems that enable adaptation to the environment, communication, learning, and cognitive integration. According to the World Health Organisation, over 1.5 billion people worldwide experienced hearing loss in 2019, including 430 million who required assistance. These numbers could rise to 2.5 billion and 700 million, respectively, by 2050. The study revealed that auditory perception has a structured neuroanatomical organisation, including ventral and dorsal sound processing pathways, functional asymmetry of the temporal lobes, and specialised modules for processing different elements of auditory messages. Hearing loss among both military personnel and civilians, as a result of full-scale invasion, is of particular concern due to its potential link to neurodegeneration and the development of dementias. Each profile of neurodegeneration manifests in distinct patterns of auditory-processing dysfunction resulting from damage to specific processing modules. The aim of the study was to contribute to the scientific discourse on the ongoing evolution of auditory perception research, analyse the cortical correlates of hearing impairment or loss, and explore the interrelationship between dementia and auditory disorders. Results. This theoretical review highlighted the challenges of early investigation of the auditory perception system due to its neuroanatomical redundancy, The frequent masking of auditory disorders as speech and language impairments, and the gradual shift from a continuous to a modular theory of sound processing. The review also outlined the cognitive architecture of auditory information processing and its modular organisation, and demonstrated a bidirectional relationship between dysfunction of the auditory system and diverse forms of dementia. Conclusions. It can be argued that auditory perception is a complex, modular system that is sensitive to neurodegenerative changes, particularly in the temporal lobe. Hearing loss is not merely a sensory issue but also a cognitive phenomenon that can serve as a predictor of dementia. Double dissociations and the interaction between peripheral and central components of hearing necessitate a multifactorial approach to diagnosis and intervention. Two areas of assistance are proposed: cognitive-compensatory (for the central effect of biological ageing) and sensory (for the central effect of peripheral pathology). Auditory therapy is considered a promising non-pharmacological method for improving the quality of life of individuals with dementia and hearing loss. One of the limitations is that the article is narrative and overview in nature, with no empirical research conducted by the author.